European consensus on the concepts and measurement of the pathophysiological neuromuscular responses to passive muscle stretch - Noort, Josien C. van den; Krautwurst, Britta (European journal of neurology, 2017)
Background and purpose To support clinical decision-making in central neurological disorders, a physical examination is used to assess responses to passive muscle stretch. However, what exactly is being assessed is expressed and interpreted in different ways. A clear diagnostic framework is lacking. Therefore, the aim was to arrive at unambiguous terminology about the concepts and measurement around pathophysiological neuromuscular response to passive muscle stretch. Methods During two consensus meetings, 37 experts from 12 European countries filled online questionnaires based on a Delphi approach, followed by plenary discussion after rounds. Consensus was reached for agreement ≥75%. Results The term hyper-resistance should be used to describe the phenomenon of impaired neuromuscular response during passive stretch, instead of for example ‘spasticity’ or ‘hypertonia’. From there, it is essential to distinguish non-neural (tissue-related) from neural (central nervous system related) contributions to hyper-resistance. Tissue contributions are elasticity, viscosity and muscle shortening. Neural contributions are velocity dependent stretch hyperreflexia and non-velocity dependent involuntary background activation. The term ‘spasticity’ should only be used next to stretch hyperreflexia, and ‘stiffness’ next to passive tissue contributions. When joint angle, moment and electromyography are recorded, components of hyper-resistance within the framework can be quantitatively assessed. Conclusions A conceptual framework of pathophysiological responses to passive muscle stretch is defined. This framework can be used in clinical assessment of hyper-resistance and will improve communication between clinicians. Components within the framework are defined by objective parameters from instrumented assessment. These parameters need experimental validation in order to develop treatment algorithms based on the aetiology of the clinical phenomena.